(untitled) (Revista Electrónica REDINE, 2018)
This article is a reserch about the work processes within the Experimental Sculpture Workshop (Humanities and Arts Faculty DEHA-UCLA), where experience systematization was employed from activities made within it, the production of experimental charts was used as a tool for comprehending the materials transformation both experimentally and interpretively, using mixed method to achieve a deeper study of artistic production. An initial insert is made to distinct arts research and arts for arts’ sake, to explain the basic concept of research-creation by contextualizing the systematization made from the activities done in the workshop, presenting inputs which explain the mixed character of the lived experience, contributing in the comprehension of three-dimensional plastic arts creative act. The methodology applied is shown in the workshop exercises starting from the Interpretive Paradigm, being a descriptive field research, which brings two procedures: experimental and hermeneutic theory, it establishes a research which is thought to be merely plastic, it also brings out scientific research within the manipulation of causal, external or resulting premises expressed in summary charts the developed process.